Social Service and Early Implementation of the Financial System - Susilowati, Susilowati; Kamela, Hurian; Puspa Pujia, Dede; Fungsiawan, Fungsiawan; Kartika Andri, Hendri (Abdi Masyarakat, 2023)
Community Service in the form of social service carried out by HIMAKU University of Tangerang Raya and a team of lecturers is beneficial for the Yapiska Foundation because these activities help Yapiska Foundation students regarding environmental hygiene and can provide knowledge to students in terms of implementing the financial system from an early age. The purpose of this service is (1) to carry out the Tri Dharma of Higher Education, namely community service. (2) Providing education to students regarding procedures for managing finances from an early age for the Yapiska Foundation. (3) Carrying out social service activities by cleaning the school environment and providing cleaning equipment for the Yapiska Foundation, (4) To carry out the work program of the Accounting Student Association. (5) Broaden scientific insights regarding the financial system. (6) Provide education regarding the importance of protecting and preserving the surrounding environment. The result is that students at the Yapiska Foundation can learn how to manage finances from an early age, so that they can apply it in their daily life. The impact of the service is (1) For the students of the Yapiska Foundation, namely knowing the importance of environmental cleanliness in the school environment and being able to understand the procedures for managing finances from an early age. (2) For students, they can know the condition of the cleanliness of the Yapiska Foundation's environment so that they can be more sensitive to the people around the campus, (3) For lecturers, they can carry out the Three Pillars of Higher Education, namely Community Service.